Hydrogels as promising carriers for the delivery of food bioactive ingredients - Li, Min; He, Xiaoqian; Zhao, Ran; Shi, Qixin; Nian, Yingqun; Hu, Bing (Frontiers in Nutrition, 2022)
The burden of public health challenges associated with the western dietary and living style is growing. Nutraceuticals have been paid increasing attentions due to their effects in promotion of health. However, in the gastrointestinal (GI) tract, the nutraceuticals suffer from not only the harsh acidic environment of the stomach and a variety of digestive enzymes, but also the antibacterial activity of intestinal bile salts and the action of protease from the gut microbiota. The amount of the nutraceuticals arriving at the sites in GI tract for absorption or exerting the bioactivities is always unfortunately limited, which puts forward high requirements for protection of nutraceuticals in a certain high contents during oral consumption. Hydrogels are three-dimensional polymeric porous networks formed by the cross-linking of polymer chains, which can hold huge amounts of water. Compared with other carries with the size in microscopic scale such as nanoparticle and microcapsules, hydrogels could be considered to be more suitable delivery systems in food due to their macroscopic bulk properties, adjustable viscoelasticity and large spatial structure for embedding nutraceuticals. Regarding to the applications in food, natural polymer-based hydrogels are commonly safe and popular due to their source with the appealing characteristics of affordability, biodegradability and biocompatibility. Although chemical crosslinking has been widely utilized in preparation of hydrogels, it prefers the physical crosslinking in the researches in food. The reasonable design for the structure of natural polymeric hydrogels is essential for seeking the favorable functionalities to apply in the delivery system, and it could be possible to obtain the enhanced adhesive property, acid stability, resistant to bile salt, and the controlled release behavior. The hydrogels prepared with proteins, polysaccharides or the mix of them to deliver the functional ingredients, mainly the phenolic components, vitamins, probiotics are discussed to obtain inspiration for the wide applications in delivery systems. Further efforts might be made in the in situ formation of hydrogels in GI tract through the interaction among food polymers and small-molecular ingredients, elevation of the loading contents of nutraceuticals in hydrogels, development of stomach adhesive hydrogels as well as targeting modification of gut microbiota by the hydrogels.